European Union's proxy accountability for tropical deforestation. Issue 4 (7th June 2021) - Partzsch, Lena
ABSTRACT: Consuming countries are increasingly holding transnational businesses accountable for environmental damage on behalf of affected communities in exporting countries. The EU Renewable Energy Directives (RED) and the EU Timber Regulation (EUTR) particularly demonstrate such an accountability-by-proxy. Both aim to prevent worldwide deforestation. However, their design and accountability logics vary considerably. Using the case of Indonesia, the article addresses the question of whether a certain accountability relationship matters for improving outcomes such as prevention of tropical deforestation. Hereby, the article contributes to a new theoretical understanding of how logics of proxy accountability are linked to narratives about agency and what inherent normative risks are. The article shows that, different from the EUTR narrative, which reaffirms standard accountability arrangements, RED presents a hybrid approach. This hybrid approach may more effectively prevent tropical deforestation, but it comes at the price of further marginalization of directly affected communities.